Aging Affects the Role of Myeloid-Derived Suppressor Cells in Alloimmunity - Schroeter, Andreas; Roesel, Maximilian J.; Matsunaga, Tomohisa; Xiao, Yao; Zhou, Hao; Tullius, Stefan G. (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSC) are defined as a group of myeloid cells with potent immunoregulatory functions that have been shown to be involved in a variety of immune-related diseases including infections, autoimmune disorders, and cancer. In organ transplantation, MDSC promote tolerance by modifying adaptive immune responses. With aging, however, substantial changes occur that affect immune functions and impact alloimmunity. Since the vast majority of transplant patients are elderly, age-specific modifications of MDSC are of relevance. Furthermore, understanding age-associated changes in MDSC may lead to improved therapeutic strategies. Here, we provide a comprehensive update on the effects of aging on MDSC and discuss potential consequences on alloimmunity.